MANAJEMEN SYARIAH DALAM PRAKTEK PENGUPAHAN KARYAWAN PERUSAHAAN SYARIAH - Arijulmanan (Institut Agama Islam Sahid Bogor, 2021)
Sharia Management in Practice for Employing Benefit on Sharia Company (The General Takaful Insurance as Case Study). This research was carried out based on information that development of Sharia company is very fast. So, it needs Sharia Management on its operational. Sharia Management is a management which its operational by Islamic Law. The study was focused on employee benefit at The General Takaful Insurance to reach the target of company. The research approach is descriptive analitic method by library research and observation at The General Takaful Insurance. It was found from the observation that implementation of benefit employee at The General Takaful Insurance was carried out based on Sharia Management. Because there is Perjanjian Kerja Bersama (PKB) as a rule between Management and employee base on Al-Qur’an verses and Hadits. Based on the results of observation, we know that benefit law on Islamic perspective to save employer and employee. Because foundation of benefit are honest and justice. Each employee will get benefit as long as his/her job. If his/her job is good, he/she will get good benefit. But if his/her job is bad, he/she will get bad benefit. Benefit at The General Takaful Insurance are basic salary, meal, transportation, etc. There are no benefit for education, home and skill. Insya Allah, The General Takaful Insurance will up date its benefit.